Analysis of the Relationship Between The Availability of Trained Health Workers and The Tuberculosis Cure Rate in Indonesia Year 2021 - Edi Utomo Putro; Intansari Intansari; Rani Delfiyanti; Kemal Siregar (Jurnal Analis Medika Biosains (JAMBS), 2024)
Tuberculosis is an infectious disease which is one of the ten causes of death in the world. Indonesia is in the third place, in the number of tuberculosis notifications after India and the Philippines in 2019 to 2020. Thus, a global target, the End TB Strategy, was set, with the aim of reducing TB cases by 90% in 2035 and in line with the National TB Management Strategy with a target of reducing incidence TB is 65 cases per 10,000 population in 2030. One of the things that plays a role in achieving the targets is the quality and quantity of trained health workers in the TB program. This study aims to determine the relationship between the availability of trained health workers and the cure rate for tuberculosis treatment in 34 provinces in Indonesia. The method used is quantitative research with a correlation study. The data used is secondary data, analyze with bivariate test and correlation test. Based on statistical tests, it was found that the results of pvalue = 0.00001 and r = 0.68, meaning that there is a significant relationship between the availability of trained health workers and the cure rate for TB treatment with a positive correlation and strong relationship strength.